2009
DOI: 10.3384/ecp09430081
|View full text |Cite
|
Sign up to set email alerts
|

Towards Unified System Modeling and Simulation with ModelicaML: Modeling of Executable Behavior Using Graphical Notations

Abstract: This paper is a further step towards application of the Model-Based Systems Engineering (MBSE) paradigm, using standardized, graphical, and executable system modeling languages. It presents further development of Modelica graphical Modeling Language (ModelicaML), a UML Profile for Modelica, which enables an integrated modeling and simulation of system requirements and design (for systems including both hardware and software). This approach combines the power of the OMG UML/SysML standardized graphical notation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
60
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 63 publications
(60 citation statements)
references
References 4 publications
0
60
0
Order By: Relevance
“…This and the relation (28) imply that A is an architecture where both the relations (17) and (18) hold. According to the relation (25), this means that it follows that…”
Section: Conditions On Element and Environmentmentioning
confidence: 99%
See 1 more Smart Citation
“…This and the relation (28) imply that A is an architecture where both the relations (17) and (18) hold. According to the relation (25), this means that it follows that…”
Section: Conditions On Element and Environmentmentioning
confidence: 99%
“…An example of when a specification such as the one shown in Fig. 1b is used in an industrial case-study, can be found in [24] where ModelicaML [25] is used to specify and verify requirements on a subsystem of a fuel management system where the requirements express the end-to-end functionality of the fuel management system in general. Another example can be found in [26] where SysML [27] is used to specify requirements on an engine knock controller and where the requirements allocated to the controller explicitly refer to parts, such as e.g.…”
Section: Introductionmentioning
confidence: 99%
“…In the simulation approach to be presented, the target simulation language is Modelica [24] with Modelica Modeling Language (ModelicaML) [25] [26]. For simulating Modelica models there are both open source (e.g., OpenModelica [26]) and commercial tools (e.g., Dymola [27]) available.…”
Section: Related Workmentioning
confidence: 99%
“…The intent of the ModelicaML profile is slightly broader than the SysML-Modelica Transformation described in this paper; ModelicaML also aims to represent all of the Modelica language in a graphical form, including equations and algorithms. The work on ModelicaML is still ongoing and has recently extended by Schamai et al (Schamai, et al, 2009). In parallel to the development of ModelicaML, Johnson et al (Johnson, et al, 2008) proposed a mapping between SysML and Modelica.…”
Section: Introductionmentioning
confidence: 99%